Relationship between functional movement screens and physical performance tests in junior basketball athletes - Klusemann, M.; Fay, T.; Pyne, D.; Drinkwater, E. (Journal of Science and Medicine in Sport, 2011)
Deficiencies in physical performance may be attributed to poor basic movement fundamentals. Purpose: We examined correlations between Functional Movement Screen (FMS) scores and fitness test results in male and female junior basketball players. Methods: Thirty nine male and female players (age 14-17 y) undertook a battery of fitness tests including the 20m-sprint, step-in vertical jump, agility, sit and reach, line drill test and the Yo-Yo intermittent recovery level 1 test. Five d later, the seven standard FMS tests (squat, hurdle step, in-line lunge, shoulder mobility, straight-leg raise, push up, and rotary stability) were performed involving one demonstration then two formal trials. The `best` trial was scored on a scale of 0-3 with a maximum total of 21. Strength and power testing included a countermovement jump (CMJ), a 15 s push up and pull up test. The total FMS score (FMSsum7) was determined with a single score for each test where the worst score was used with those screens that involved a right and left side component. Correlations were determined between single and total FMS score and each physical performance test for both genders combined and then separately. The magnitude of correlation was interpreted as: 0-0.1 trivial, 0.1-0.3 small, 0.3-0.5 moderate, and >0.5 large. Results: No substantial correlations were found between FMSsum7 and performance tests for both genders combined. For females, moderate correlations were observed between the FMSsum7 and Yo-Yo test (r= 0.39 ± 0.34; correlation coefficient ± 90% confidence limits), and the agility test (r= -0.41 ± 0.32). Small to moderate relationships were present between the FMSsum7 and the push up, yo-yo and CMJ tests in the male subjects, but correlations were unclear given large variability. Both the push up strength test and the FMS push up screen (r= 0.30 ± 0.26) and the sit and reach test and the straight-leg raise screen (r= 0.43 ± 0.23) had a moderate correlation in both genders combined. The sit and reach test had a large relationship with the straight-leg raise screen in male subjects (r= 0.50 ± 0.32). Conclusion: FMS scores are moderately correlated with endurance and agility in females, and lower body flexibility in males. Deficiencies in some basic movement patterns may reveal potential areas of improvement for physical performance and assist coaches and support staff in training prescription.